A educação profissional e Tecnológica de alunos com deficiência visual no IFPA Campus Tucuruí – História de vida dos egressos - Martins, Ronaldo Meireles (2019)
The concern that gave rise to this research was to know whether the professional and technological education offered by the IFPA-Campus Tucuruí was significant in the lives of students with visual impairment. For that purpose, the Life History Methodology was used, through interviews with the first three students with visual impairment that were graduated in the Campus. The general objective of this research was to evaluate the Professional Education offered by the IFPA Campus Tucuruí from the perspective of the visually impaired students. The instrument used to analyze the results of the research was the technique of Content Analysis. The results showed that the IFPA Campus Tucuruí, despite the mishaps over time, succeeded in the strategies developed for the education of these students, largely as a result of the intervention and support of NAPNE, a fact that inspired the making of the Educational Product, which was materialized in a web page with a report of the experiences of NAPNE Campus Tucuruí to serve as support to other institutions.